Hypertension Associated With Hearing Loss and Tinnitus Among Hypertensive Adults at a Tertiary Hospital in South Africa - Ramatsoma, Hlologelo; Patrick, Sean Mark (Frontiers in Neurology, 2022)
Introduction Hypertension is one of the leading causes of morbidity and mortality worldwide, and has been associated with target organ damage. Effects of hypertension on the auditory system are varied and requires further investigation. This study aimed to investigate the association between hypertension and auditory deficits (hearing loss and tinnitus). Methods This study employed a cross-sectional study including 106 (54.7% female) hypertensive adults aged 18–55 years, and 92 (52.2% female) non-hypertensive sex- and age-matched adults residing in South Africa. A data extraction sheet was used to obtain hypertension information from participants' medical files, and to subjectively obtain tinnitus status and characteristics among participants. Participants' hearing sensitivity—including extended high frequencies (EHF)—were measured using a diagnostic audiometer. The χ2 test determined the difference in auditory deficit prevalence between the study groups. Logistic regression was used to identify predictor variables associated with auditory deficits in the hypertensive group. Results A hearing loss prevalence of 37.4% among hypertensive adults compared to 14.1% among the non-hypertensive group (P = 0.000, χ2 = 14.00) was found. The EHF pure-tone average among the hypertensive group was 44.1 ± 19.2 dB HL, and 20.0 ± 18.3 dB HL among the control group. Bilateral mild sensorineural hearing loss was the most common type of hearing loss among hypertensive adults. A higher prevalence of tinnitus (41.5%) was found in the hypertensive group compared to the control group (22.8%) (P = 0.008, χ2 = 7.09). In this study, 30.3% of hypertensive adults had tinnitus without hearing loss compared to 17.7% non-hypertensive adults. Factors associated with hearing loss included being between 50 and 55 years [adjusted Odds Ratio (AOR) = 3.35; 95% Confidence Interval (CI): 1.32–8.50; P = 0.011], having grade 2 hypertension (AOR = 4.18; 95% CI: 1.02–17.10; P = 0.048), and being on antihypertensive medication (AOR = 3.18; 95% CI: 1.02–9.87; P = 0.045). Tinnitus was associated with grade 3 hypertension (AOR = 3.90; 95% CI: 1.12–12.64; P = 0.033). Conclusions Our study showed that hypertensive adults had a higher proportion of hearing loss and tinnitus compared to non-hypertensive adults. Findings suggest an association between hypertension and auditory deficits, demonstrating a need for integration of hearing healthcare services for hypertension management.